2023
DOI: 10.3389/fmed.2023.1125530
|View full text |Cite
|
Sign up to set email alerts
|

The importance of chest CT severity score and lung CT patterns in risk assessment in COVID-19-associated pneumonia: a comparative study

Abstract: IntroductionChest computed tomography (CT) is suitable to assess morphological changes in the lungs. Chest CT scoring systems (CCTS) have been developed and use in order to quantify the severity of pulmonary involvement in COVID-19. CCTS has also been correlated with clinical outcomes. Here we wished to use a validated, relatively simple CTSS to assess chest CT patterns and to correlate CTSS with clinical outcomes in COVID-19.Patients and methodsAltogether 227 COVID-19 cases underwent chest CT scanning using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
(100 reference statements)
1
3
0
Order By: Relevance
“…This is similar to other studies [42,47]. Finally, CT score positively correlated with age, WBC and platelet counts, CRP, PCT, LDH, D-dimer, ferritin, IL-6, urea, and the A-DROP score, while negatively correlated with total lymphocyte count, PaO2 and SaO2 [39].…”
Section: рис 5 компьютерная томограмма органов грудной клетки аксиаль...supporting
confidence: 90%
See 2 more Smart Citations
“…This is similar to other studies [42,47]. Finally, CT score positively correlated with age, WBC and platelet counts, CRP, PCT, LDH, D-dimer, ferritin, IL-6, urea, and the A-DROP score, while negatively correlated with total lymphocyte count, PaO2 and SaO2 [39].…”
Section: рис 5 компьютерная томограмма органов грудной клетки аксиаль...supporting
confidence: 90%
“…However, when comparing non-vaccinated patients from both nations, we revealed that most of the cases lie at mid-score and above with no significant difference (p=0.639). In Szabo et al, the mean score was moderate (14.6) while in the study of Francone et al, the mean score was 18 which was associated with a high mortality rate [39,42].…”
Section: рис 5 компьютерная томограмма органов грудной клетки аксиаль...mentioning
confidence: 86%
See 1 more Smart Citation
“…Miklos Szabo et al. found that the chest CT scoring system (CCTS) and specific chest CT patterns can predict ventilation requirements and mortality in COVID-19 ( 32 ). In this study, we used the TSS semi-quantitative method to assess the severity of lung lesions in patients with COVID-19 and then correlate it with hyponatremia.…”
Section: Discussionmentioning
confidence: 99%